برنامج تأهيلي حركي وفق نموذج مقترح لمسببات آلام أسفل الظهر وتأثيره على العجز الحركي - عبدالتواب، أيمن فاروق مكاوي (جامعة حلوان - كلية التربية الرياضية للبنين, 2020)
الآم أسفل الظهر هي الشكوى الأكثر شيوعًا بين الناس ولا تؤثر فقط على الشخص طبيًا ولكن أيضًا اجتماعيًا واقتصاديًا وتتسبب في تكاليف باهظة على نظام الصحة من حيث طرق التشخيص، وتكلفة العلاج الطبي إضافة لذلك زيادة حالات التغيب عن العمل. كما تعد آلام أسفل الظهر عامل رئيسي للعجز الحركي في جميع الفئات العمرية. يهدف البحث إلى تحديد مسببات آلام أسفل الظهر وتأثيرها على العجز الحركي من خلال تصميم نموذج مقترح لهذه المسببات ووضع برنامج تأهيلي حركي مع تعديل بعض الممارسات الحياتية للحد من هذه المسببات. تعتمد هذه الدراسة على المنهج الكمي لاختبار فرضيات الدراسة من خلال استخدام الاستبيان كطريقة لجمع البيانات للتحقق من العوامل المسببة لآلم أسفل الظهر والعجز على عينة قوامها 215 فرد يعانون من آلام أسفل الظهر. كما استخدم الباحث المنهج التجريبي باختيار القياس القبلي– البعدي على مجموعة تجريبية واحدة قوامها 15 فرد يعانون من آلام أسفل الظهر تم قياس درجة آلام أسفل الظهر بمقياس أوسويستري لإعاقة آلام أسفل الظهر. خضع المشاركون في الدراسة للبرنامج التأهيلي لمدة 12 أسبوع بواقع ثلاث وحدات أسبوعيا. النتائج: تم التوصل إلي نموذج قياس مقترح لمسببات آلام أسفل الظهر حيث تم الكشف عن وجود تأثير كبير بين العوامل المسببة لآلم اسفل الظهر والعجز، كما استنتج أن تعرض أفراد عينة الدراسة المصابين بآلام أسفل الظهر للبرنامج المقترح الذي اشتمل علي جانب التمرينات التأهيلية والإرشادات الصحية أدي إلي انخفاض معنوي دال في درجة آلام أسفل الظهر، أوصي الباحث بالاستفادة من تطبيق البرنامج المقترح الذي اشتمل علي التمرينات التأهيلية والإرشادات الصحية لتخفيف آلام أسفل الظهر وتعديل بعض السلوكيات الحياتية للحد من هذه الآلام وسرعة تقييم آلام أسفل الظهر وسرعة البدء في التعافي بعد الإحساس الأول بهذه الآلام.
low back pain is the most common complaint among people. It affects not only the person medically but also socially and economically and it causes huge costs for the health system in terms of diagnostic methods, and the cost of medical treatment In addition, the increase in absenteeism cases. Low back pain is also a major factor in motor impairment in all age groups. The research aims to determine the causes of low back pain and its effect on motor deficits by designing a proposed model for these causes and setting a dynamic rehabilitation program with amending some life practices to reduce these causes. This study relies on the quantitative approach to test the hypotheses of the study through the use of the questionnaire as a way to collect data to investigate factors causing low back pain and disability on a sample of 215 individuals with low back pain. The researcher also used the experimental method by selecting the prepost measurement on one experimental group. Low back pain was assessed by Oswestry low back Disability questionnaire. The participants in our study received a rehabilitation program 12-week, 3-times-per-week.The results: Have been reached A suggested measurement model for low back pain etiology, where a significant effect was detected among the factors causing low back pain and disability It was also concluded that members of the study sample with low back pain were exposed to the proposed program, which included the aspect of rehabilitative exercises and health advice, which led to a significant decrease in the degree of low back pain. The researcher recommended taking advantage of the application of the proposed program that included rehabilitation exercises and health instructions to relieve low back pain and modify some life behaviors to reduce this pain and the speed of assessing low back pain and the speed of starting to recover after the initial feeling of this pain.
Keywords: التربية الحركية -- الصحة الرياضية -- البرامج التأهيلية -- آلام الظهر